1982
DOI: 10.1002/cyto.990030108
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of RNA content in different cell populations using pyronin Y and methyl green

Abstract: Pyronin Y (PY) was used, in flow cytometric (FCM) systems, to estimate the RNA content per cell in formalin fixed EL4 leukosis tumor cells, enzyme dispersed R3327-G rat prostatic adenocarcinoma cells, mouse spleen cells stimulated with concanavalin A, and human peripheral blood lymphocytes stimulated with phytohemagglutinin. Preincubation of the cells with methyl green (MG) blocked PY binding to DNA such that the intracellular fluorescence from MG-PY was due primarily to its binding to RNA. Treatment of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In an accompanying paper (171, we describe biophysical and biochemical studies on pyronin Y (PY) and interactions of this dye with natural and synthetic nucleic acids in solutions. Several observations from these studies could be of importance for the qualitative and quantitative application of PY, both as an absorption dye for light microscopy (2,191 and as a fluorochrome (4,23,26,28). In the present paper, we demonstrate that the biophysical properties of the dye complexes with nucleic acids observed in solutions (17) are relevant in cytochemistry.…”
supporting
confidence: 53%
“…In an accompanying paper (171, we describe biophysical and biochemical studies on pyronin Y (PY) and interactions of this dye with natural and synthetic nucleic acids in solutions. Several observations from these studies could be of importance for the qualitative and quantitative application of PY, both as an absorption dye for light microscopy (2,191 and as a fluorochrome (4,23,26,28). In the present paper, we demonstrate that the biophysical properties of the dye complexes with nucleic acids observed in solutions (17) are relevant in cytochemistry.…”
supporting
confidence: 53%
“…Previous studies have shown that total RNA values are raised as a function of the tumour proliferation rate. [20][21][22][23] Thus, the NAI provides a quantitative correlate for the proliferative potential of melanocytic lesions. Indeed, strong inverse correlations were found between NAI and both mitotic index and Breslow thickness.…”
Section: Discussionmentioning
confidence: 99%
“…DiO-CI(3) [21], thioflavin T [27], and thiazole orange [23] have been used for viable reticulocyte analysis. Pyronin Y (PY) has also been used for automatic counting of reticulocytes by Tanke et al [31], but this dye, specific for double-stranded RNA, is also used in association with other dyes like methyl green for RNA content analysis [26], or with Hoechst 33342 for RNA versus DNA analysis in unfixed cells [29]. One inconvenience of PY is that staining is not always stoichiometric, as PY seems to be sensitive to the conformation of the rRNA, and its fluorescence drops whefla polysomes dissociate [13].…”
Section: Total Rna Measurementsmentioning
confidence: 99%